METHODS FOR ESTIMATING COORDINATION OF FUZZY EXPERT KNOWLEDGE MODELS - V.P. DIMITROV; L.V. BORISSOVA; I.N. NURUTDINOVA (Advanced Engineering Research)
Some aspects of the methods for calculating indices of expert information difference and coordination are considered. Analytical expressions of the mentioned indices for 13 typical variants of belonging functions’ pair arrangement have been obtained. The methods applying example is given.